HUMAN BEHAVIOUR CONTRIBUTING TO DOMESTIC VIOLENCE AGAINST MEN IN THE PRESENT CONTEXT: A PHENOMENOLOGICAL STUDY - Shrivastava, Deepika; Shukla, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
When a person makes any effort to maintain control over a person close to him. These efforts can be abusive words, threats, physical impact or mental impact. Domestic violence is experienced by those people who are controlled by their close ones, that too without their consent or it can be said that ‘domestic violence’ occurs between people who are in or living in a close relationship. This type of violence can take many forms. It can happen to anyone. Most of the victims of domestic violence are women. This is the general perception of people in society. But sometimes it is not easy to identify domestic violence against men.